Dielectric Spectroscopy Analyses of SrBi4Ti4O15 Films Obtained from Soft Chemical Solution - A. Z. Simões; C. S. Riccardi (Advances in Materials Science and Engineering)
SrBi4Ti4O15 (SBTi) thin films were deposited by the polymeric precursor method on Pt bottom electrodes. The obtained films were characterized by X-ray diffraction, scanning electron microscopy, Raman spectroscopy, and dielectric spectroscopy analyses. The capacitance-voltage (C-V) characteristics of perovskite thin film showed normal ferroelectric behavior. The remanent polarization and coercive fields were 5.4 μC/cm2 and 85 kV/cm, respectively. Dielectric spectroscopy was employed to examine the polycrystalline behavior of ferroelectric material and the mechanisms responsible for the dielectric performance of the thin film.